PHYSICAL, ORGANOLEPTIC AND FOOD FIBER CHARACTERISTICS OF SWEET BREAD WITH ADDITION OF BAMBOO FLOUR (Dendrocalamus asper) - Deska Fransiska; Marniza Marniza; Devi Silsia (Jurnal Agroindustri, 2021)
Bread is made from wheat flour and other ingredients whose dough is fermented and baked. Sweet bamboo flour is a food product made from sweet bread raw material with substitution variations in the concentration of bamboo shoot betung flour.  This study aims to determine the effect of bamboo flour substitution on the physical, chemical and organolytic properties of sweet bread. This study used Completely Randomized Design (CRD) consisting of one factor, namely the additon of   bamboo flour with concentration of 0%, 5%, 10%, 15%, 20% Each treatment was carried out 3 times so that the total number of experimental units was 15 units. The results showed that the addition of bamboo flour had an effect on the level of improvement of sweet bread with the highest value of 114.88%,  and the water content less than 40%. The brightness of the sweet bread color is found without the addition of bamboo flour with a value of 7.5 Y 9/4 and the darkest result is the addition of 20% bamboo flour with a value of 2.5 Y 3/6. Based on the results of organoleptic, the bamboo shoot flour significantly affected the color and texture of sweet bread but did not significantly affect the aroma, taste and overall.  The fiber content of sweet bread with bamboo shoot flour was higher than the control, namely 13.34-19.29% and the control 8.54%.